The Reality of Implementing the Knowledge Management Operations at Government School in Al-Karak Directorate from Principal's Perspective - Almaiath, Amjad Tahseen Mohammad (Journal of Educational and Psychological Sciences, 2021)
This Study aimed to identify The Reality of Implementing the Knowledge Management Operations at Government School in Al-Karak Directorate from Principal's Perspective, and to determine the effect of variables (sex, and years of experience), the researcher used the Descriptive approaches, to collect data Questioner used which consisted from (26) paragraph, the sample of study consist from (92) female and male, (52) Female and (40) male, chosen intentionally, the result of SPSS analysis shown that the level of Implementing the Knowledge Management Operations at Government School in Al-Karak Directorate from Principal's Perspective was high with total average (3.92 out of 5). The finding also showed there was no statistically significant differences at (α≤0.05) refer to principal sex (male and female) in addition there were statistically significant differences between the principals years of experience in favor of (11 years and more). Based on the results, the researcher presented a number of recommendations and proposals, to enhance the Implementing the Knowledge Management Operations at Government School in public schools in Al-Karak directorate, and the whole of the Kingdom and the Arab countries.
Keywords: Knowledge Management Operations; Government School; Al-Karak Directorate; Schools Principal's